Local treatment of a pleural mesothelioma tumor with ONCOS-102 induces a systemic antitumor CD8(+) T-cell response, prominent infiltration of CD8(+) lymphocytes and Th1 type polarization - Ranki, Tuuli (Oncoimmunology, 2014)
Late stage cancer is often associated with reduced immune recognition and a highly immunosuppressive tumor microenvironment. The presence of tumor infiltrating lymphocytes (TILs) and specific gene-signatures prior to treatment are linked to good prognosis, while the opposite is true for extensive immunosuppression. The use of adenoviruses as cancer vaccines is a form of active immunotherapy to initialise a tumor-specific immune response that targets the patient's unique tumor antigen repertoire. We report a case of a 68-year-old male with asbestos-related malignant pleural mesothelioma who was treated in a Phase I study with a granulocyte-macrophage colony‑stimulating factor (GM-CSF)-expressing oncolytic adenovirus, Ad5/3-D24-GMCSF (ONCOS-102). The treatment resulted in prominent infiltration of CD8(+) lymphocytes to tumor, marked induction of systemic antitumor CD8(+) T-cells and induction of Th1-type polarization in the tumor. These results indicate that ONCOS-102 treatment sensitizes tumors to other immunotherapies by inducing a T-cell positive phenotype to an initially T-cell negative tumor.